Sexual deception in a cannibalistic mating system? Testing the Femme Fatale hypothesis - Barry, Katherine L. (Proc Biol Sci, 2015)
Animal communication theory holds that in order to be evolutionarily stable, signals must be honest on average, but significant dishonesty (i.e. deception) by a subset of the population may also evolve. A typical praying mantid mating system involves active mate searching by males, which is guided by airborne sex pheromones in most species for which mate-searching cues have been studied. The Femme Fatale hypothesis suggests that female mantids may be selected to exploit conspecific males as prey if they benefit nutritionally from cannibalism. Such a benefit exists in the false garden mantid Pseudomantis albofimbriata—females use the resources gained from male consumption to significantly increase their body condition and reproductive output. This study aimed to examine the potential for chemical deception among the subset of females most likely to benefit from cannibalism (poorly fed females). Females were placed into one of four feeding treatments (‘Very Poor’, ‘Poor’, ‘Medium’ and ‘Good’), and males were given the opportunity to choose between visually obscured females in each of the treatments. Female body condition and fecundity varied linearly with food quantity; however, female attractiveness did not. That is, Very Poor females attracted significantly more males than any of the other female treatments, even though these females were in significantly poorer condition, less fecund (in this study) and more likely to cannibalise (in a previous study). In addition, there was a positive correlation between fecundity and attractiveness if Very Poor females were removed from the analysis, suggesting an inherently honest signalling system with a subset of dishonest individuals. This is the first empirical study to provide evidence of sexual deception via chemical cues, and the first to provide support for the Femme Fatale hypothesis.